The SAM domain of ANKS6 has different interacting partners and mutations can induce different cystic phenotypes - Bakey, Zeineb; Hoffmann, Sigrid (Kidney international, 2015)
The ankyrin repeat and sterile α motif (SAM) domain-containing six gene (Anks6) is a candidate for polycystic kidney disease (PKD). Originally identified in the PKD/Mhm(cy/+) rat model of PKD, the disease is caused by a mutation (R823W) in the SAM domain of the encoded protein. Recent studies support the etiological role of the ANKS6 SAM domain in human cystic diseases, but its function in kidney remains unknown. To investigate the role of ANKS6 in cyst formation, we screened an archive of N-ethyl-N-nitrosourea-treated mice and derived a strain carrying a missense mutation (I747N) within the SAM domain of ANKS6. This mutation is only six amino acids away from the PKD-causing mutation (R823W) in cy/+ rats. Evidence of renal cysts in these mice confirmed the crucial role of the SAM domain of ANKS6 in kidney function. Comparative phenotype analysis in cy/+ rats and our Anks6(I747N) mice further showed that the two models display noticeably different PKD phenotypes and that there is a defective interaction between ANKS6 with ANKS3 in the rat and between ANKS6 and BICC1 (bicaudal C homolog 1) in the mouse. Thus, our data demonstrate the importance of ANKS6 for kidney structure integrity and the essential mediating role of its SAM domain in the formation of protein complexes.